Analysis of Students' Science Literacy Skills on the Circulatory System Material at SMA Negeri 1 Luwuk - Moh. Fahri Haruna; Abd. Muin Kenta; Nurlia Nurlia; Sulasmi Anggo; Reina Novrianti S Bungaji (Riviera Publishing, 2024)
Science literacy is an ability that involves various aspects, including knowledge (concepts, facts, and vocabulary), processing skills (thinking and intellectual skills), dispositions (behaviors and attitudes), and the ability to connect them with the reality around us. Effective education is essential to improve the quality of human resources in the era of rapid development of science and technology. This study evaluates students' science literacy skills on circulatory system material at SMA Negeri 1 Luwuk. This study used a descriptive qualitative research method. The sample consisted of 68 students selected from the population of class XI IPA students at SMA Negeri 1 Luwuk in the 2022/2023 school year. The data collection technique used a science literacy test consisting of 27 questions. Data were analyzed using descriptive statistical analysis techniques. The results showed that overall, students' science literacy skills in circulatory system material were in the poor category. This evaluation is based on four indicators of science literacy with the following percentage results: nominal indicator 37.68% (poor), functional indicator 14.91% (abysmal), and conceptual indicator 13.80% (abysmal). The implication of this study is the need for improved teaching methods and the use of more effective learning media to improve students' science literacy. The findings can be used for curriculum improvement and school teaching strategies.